Simultaneous administration of oral rhesus-human reassortant tetravalent (RRV-TV) rotavirus vaccine and oral poliovirus vaccine (OPV) in Thai infants - Sricharoen Migasena (2018)
Rhesus-human reassortant tetravalent (RRV-TV) oral rotavirus vaccine was given at the same time as oral poliovirus vaccine (OPV) or inactivated parenteral poliovirus vaccine (IPV) to Thai infants at 2, 4 and 6 months of age. Sera for rotavirus antibody studies were taken prior to and one month after each vaccination. After the first dose of vaccine at 2 months of age, 37% of the infants receiving rotavirus vaccine with IPV but only 10% of those receiving it with OPV showed a seroconversion by rotavirus IgA ELISA antibody test (p<0.001). Likewise, neutralizing antibody seroconversion rates in initially seronegative subjects to rhesus rotavirus type 3 (RRV-3) after the first dose of RRV-TV vaccine were higher if the vaccine was given with IPV (74%) than if given with OPV (39%) (p=0.0069). After the second and third doses of vaccine, the rotavirus IgA ELISA and RRV-3-neutralizing antibody response rates were not different between groups. Development of neutralizing antibodies to human rotavirus serotypes 1, 2 and 4 in the first seven months of life in vaccinees receiving rotavirus vaccine with OPV tended to occur at a lower rate than in those receiving rotavirus vaccine with IPV but the antibody levels were not significantly different at 7 months of age. Poliovirus type 2 and type 3 antibody responses were not different in infants receiving the rotavirus vaccine with OPV as compared with infants receiving only OPV. The mean poliovirus type 1 antibody level was slightly but not significantly lower at 5 and 7 months of age in infants that received both rotavirus vaccine and OPV. These results suggest that OPV is likely to interfere with the take of RRV-TV rotavirus vaccine but the interfering effect can largely be compensated for by giving multiple doses of RRV-TV vaccine or, possibly, by using a higher-titre rotavirus vaccine. Interference of RRV-TV vaccine with OPV may not pose a significant problem, but further research is required to ascertain that antibody responses to poliovirus type 1 are not affected by RRV-TV especially if a higher-titre vaccine is used. © 1995.